AGE, EVOLUTION AND REGIONAL SETTING OF THE PALAEOPROTEROZOIC UMBA IGNEOUS SUITE IN THE KOLVITSA-UMBA ZONE, KOLA PENINSULA: CONSTRAINTS FROM NEW GEOLOGICAL, GEOCHEMICAL AND U-PB ZIRCON DATA - Glebovitsky V.; Alexejev N.; Sedova I.; Salnikova E.; Berezhnaya N.; Marker M.; Bridgwater D. (My University, 2001)
The Umba igneous complex consists of an enderbite–charnockite suite, including porphyritic variety of charnockites, and a porphyritic granite. Both are intruded by irregular veins or minor bodies of later reddish granite. The porphyritic charnockites locally contains abundant xenoliths of country rocks and its contamination by sedimentary material is expressed by a minor content of garnet, that increases in amount in areas with sedimentary inclusions. The Umba igneous complex and the Umba block metasediments were deformed together during two episodes of deformation. The first one was a major episode of thrusting with the formation of a penetrative shear foliation (S1), which dips gently eastwards, and a gently SE-plunging lineation. Coeval with this thrusting, the boundary between the Umba block and the Poriya Guba series in the southeast developed as a strike-slip shear zone, that juxtaposed the two blocks along a tectonic melange zone. The S1-shearing deformed the enderbite–charnockite suite, and probably also the porphyritic granite, into plate-like, eastward-dipping bodies. Predating the shearing, the metasediments underwent high-grade metamorphism and anatexis leading to a high degree of partial melting. This anatexis is also found in the enderbite–charnockite suite, but in a much smaller scale and mainly in the marginal parts of the bodies. The second episode of deformation formed narrow localized extensional shear zones (S2), which are developed in all rock units. The S1-shearing in the tectonic melange zone occurred under high-pressure metamorphism during cooling at constant pressure (T=806–818°C, P=9.3–9.5 kbar) and then at decreasing pressure due to tectonic uplift. Both seem to have gone through the same deformation events as the metasediments. The S2-extension occurred under decompression (P=7.5–8.0 kbar, T=860–840°C) caused by uplift or tectonic erosion of the thrust pile. Though indistinguishable in the field the enderbite–charnockite suite form a discontinuous suite with a trondhjemitic trend for the former, and a calc–alkaline trend for the latter. Geochemical study shows that the charnockite group is more strongly differentiated than the enderbite group and that magmatic differentiation in the charnockites were controlled by K-feldspar fractionation. The enderbites, on the other hand, lack differentiation and are considered to have crystallized rapidly from its magma source. The charnockites came from a different source that, judging from the high K/Rb ratio, formed at a deeper crustal level than the enderbites. Both members of the enderbite–charnockite suite formed due to subduction in an island arc setting, and Sm–Nd model ages of 2.1–1.9 Ga indicate that the Palaeoproterozoic suite has a juvenile character. Conventional U-Pb zircon dating of the porphyritic charnockite has given discordant ages of 1912.5±7.7 Ma, 1949±7 Ma and 1966±9. Our preferred interpretation is that the 1912.5±7.7 Ma age represents the age of intrusion, or maximum intrusion age of the charnockites, and that the 1949±7 Ma and 1966±9 Ma ages for the abraded type represent ages or mixed ages of inherited zircons from the contaminating Umba block metasediments. The youngest detrital zircons in these metasediments have similar ages. Their source could have been early magmatic arc intrusives, which were eroded shortly after their formation. If the Umba metasediments were deposited in a magmatic arc setting their initial deformation in an evolving arc may have provided the necessary heat flow for anatexis and high-grade peak metamorphism of the metasediments. Therefore, the intrusions of the enderbite–charnokite suite during the later evolution of the magmatic arc could have post-dated the peak of metamorphism, but still pre-date collision and thrusting leading to tectonic telescoping of the units, and thus explain the lower metamorphic grade in the Umba igneous complex compared to the metasediments. If the 1912.5±7.7 Ma age represents the maximum time of intrusion, the true intrusion age might be slightly younger.
Keywords: Umba igneous complex; Porphyritic granite; Xenoliths; Palaeoproterozoic; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская